Hemochromatosis Patients as Voluntary Blood Donors - Tara E Power; Paul C Adams (Canadian Journal of Gastroenterology)
The present study was designed to investigate hemochromatosis patients' suitability as blood donors as well as their perceptions and experience with the current public donation system. Participants were gathered from a list of current hemochromatosis patients (n=120) and members of the Canadian Hemochromatosis Society (n=1000). Of the 1120 surveys mailed out to these groups, 801 surveys were returned completed. The sample respondents had a mean age of 57.44 years (SD=12.73; range 19 to 87 years), and 57% were men. It was found that 20% (160) of the respondents have donated blood since their diagnosis; however, only 12% of the respondents indicated that they use voluntary blood donation as a means of maintaining their iron levels. Forty per cent of the respondents indicated that they had been refused from voluntary donation. Despite the fact that in May 2001 the Canadian Blood Services, in collaboration with the Canadian Hemochromatosis Society, began a promotion campaign to encourage hemochromatosis patients to become voluntary blood donors, the present study found that 15% of the respondents reported having been refused from the voluntary blood donation service due to the diagnosis of hemochromatosis. With respect to quality of life, it was found that individuals who donate blood were generally healthier with respect to physical functioning and bodily pain, however, these findings may indicate that hemochromatosis patients who are healthier are better able to donate at public blood banks, rather than that voluntary blood donation has an effect on the donors' physical functioning over phlebotomy clinic users. These study findings suggest that although there may be other medical factors limiting individuals from donating, hemochromatosis patients are interested in being voluntary blood donors and this potential resource is currently under-used.